2013
DOI: 10.1182/blood-2013-03-493312
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated uptake of VWF/platelet complexes in macrophages contributes to VWD type 2B–associated thrombocytopenia

Abstract: Key Points• Adsorption of VWF type 2B mutants to platelets induces thrombocytopenia in VWD type 2B mice.• VWF/platelet complexes are phagocytosed by macrophages in liver and spleen.Von Willebrand disease (VWD) type 2B is characterized by mutations causing enhanced binding of von Willebrand factor (VWF) to platelets. Bleeding tendency is associated with heterogeneous clinical manifestations, including moderate to severe thrombocytopenia. The underlying mechanism of the thrombocytopenia has remained unclear. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 36 publications
3
65
0
1
Order By: Relevance
“…28 It has been suggested that the mutant VWF is cleared faster in these patients because of the spontaneous binding of VWF to platelets. 29 Our results also showed that the mutant type 2N VWF is cleared faster than normal VWF.…”
Section: Discussionsupporting
confidence: 69%
“…28 It has been suggested that the mutant VWF is cleared faster in these patients because of the spontaneous binding of VWF to platelets. 29 Our results also showed that the mutant type 2N VWF is cleared faster than normal VWF.…”
Section: Discussionsupporting
confidence: 69%
“…have given rise to a prothrombotic condition, it is now accepted that several causes underlie the thrombocytopenia, such as an increased platelet clearance of vWF/platelet complexes (10). However, the presence of giant platelets also point to vWF-type 2B mutants playing a role in the fine regulation of the processes that result in platelet production.…”
Section: Discussionmentioning
confidence: 99%
“…In VWD-type 2B, gainof-function mutations in the GPIbα-binding A1 domain of vWF increase the affinity for this platelet receptor, provoking spontaneous interactions between vWF and platelets and loss of high-molecular-weight vWF multimers (9). The underlying causes of thrombocytopenia in VWD-type 2B are multiple, such as the incorporation of platelets bound to plasma vWF into circulating aggregates that display an increased platelet clearance (10,11). While platelet apoptosis does not seem to be involved (12), defective platelet production appears central to the mechanism of thrombocytopenia in VWD-type 2B.…”
Section: Introductionmentioning
confidence: 99%
“…3 Here Lechtenberg and colleagues neatly surmount these problems and determine the structure of a reengineered form of pseutarin C, a preassembled soluble snake venom prothrombinase. 1 The actual structure determined is between the 2 P textilis components in their preactivated state: factor V in complex with a truncated form of factor X. In an elegant series of experiments, the authors validate the relevance of their system, showing that the relevant forms of pseutarin C that they investigate are capable of cleaving and activating human prothrombin.…”
mentioning
confidence: 93%
“…The study by Casari and colleagues is aimed at filling these gaps. 1 They developed a murine model for VWD2B that reproduces the phenotype observed in human patients with the disorder. As an important background to the study, the same group previously reported that macrophages in liver and spleen bind and endocytose VWF and that chemical blockade of these cells leads to a twofold prolongation of VWF half-life in circulation.…”
mentioning
confidence: 99%